Optimization of Outpatient Administrative Workflow in the Digital Era: A Comparative Analysis of Registration Waiting Times via the Mobile JKN Application vs. On-Site Registration - Antik Pujihastuti; Mila Sari (Journal of Health Service Administration and Hospital Management, 2025)
The digitalization of healthcare is crucial for improving service efficiency, a necessity highlighted by administrative burdens in Indonesia's JKN-KIS program causing long patient waiting times. This study addresses the need for quantitative evidence by comparing the operational efficiency of Mobile JKN application (Digital Pathway) versus conventional on-site registration (Physical Pathway). Using an ex-post facto quantitative comparative design on aggregated secondary RWT data from official health reports (2020–2025; N=170,995), the analysis employed the non-parametric Mann-Whitney U Test. Results showed a statistically significant difference (p < 0.001), with the Mobile JKN RWT averaging 5.38 minutes compared to 18.91 minutes for the on-site method. This represents a substantial efficiency gain, quantified by a very large effect size (Cohen's d = 3.15). The findings validate Mobile JKN as an effective parallel service channel for mitigating system bottlenecks. Implications include justifying health policy mandates for digital adoption and supporting the revision of Minimum Service Standards. Future research should focus on end-to-end service time analysis and sustained digital adoption drivers.